Hepatoprotective effect of opioid peptides in stress - Alexey V. Solin; Yury D. Lyashev; Nikolay V. Tsygan (Belgorod National Research University, 2019)
Introduction: Influence of the endogenous opioid system on the liver has not been studied enough. To understand the damaging effects of stress on the liver and the hepatoprotective effects of opioids, a study was performed on stress-resistant and stress-susceptible animals. Materials and methods: The investigation was performed on 725 Wistar male-rats. Various types of stress were modeled: acute immobilization stress of various duration (3, 6 and 12 hours), chronic stress of limited mobility, swimming stress and traumatic stress (resection of 70% of the liver). Agonists of various types of opioid receptors in equimolar doses were injected to stressed animals at equimolar doses: DAGO - a mu-receptor agonist - at a dose of 6.3 mcg/kg, DSLET - a delta-receptor agonist - at a dose of 10 mcg/kg, and kappa receptor agonist dynorphin A (1-13) - at a dose of 20.1 mcg/kg. Results and discussion: The stress-limiting action of the studied opioids is characterized by the reduced hepatocyte dystrophy, microcirculation correction, a decreased concentration of lipid peroxidation metabolites, a suppressed cytolytic syndrome, a stimulated synthetic ability of the liver, and is more pronounced in stress- susceptible animals. The greatest stress-protective effect is shown after administering dynorphin A (1-13) in immobilization stress, and DAGO - in swimming stress. Dynorphin A (1-13) and DAGO manifested the most pronounced effect on the liver regeneration after resection. A preliminary stress simulation accelerates liver regeneration at the initial stage after resection. Conclusion: The hepatoprotective effect of opioids in stress depends on the typological peculiarities of animals. The results obtained offer a challenge of synthesizing new hepatoprotectors.